The effect of compound plyometric exercises with weights on improving the muscle power and performance of some offensive skills among talented basketball players - Yousra Hassoun Mutashar Abstract (Mustansiriyah Journal of Sports Science, 2024)
The research included the introduction and the importance of the research in that the game of basketball needs to move with the ball to perform all offensive skills, especially scoring, so you need to develop all of the muscles of the arms, legs, abdomen, as well as the muscles of the shoulders and back, and this is done by performing special exercises, and one of the most appropriate exercises To develop muscular power is to use compound exercises and implement them at a certain speed, and muscular power requires the ability of the muscular system to overcome resistances that require a high degree of speed of muscle contractions. It is consistent with the nature of skillful performance.In basketball, it is required that the player obtain physical and skill ability with a high degree and combine them together to obtain the best results in implementing offensive movements and skills and scoring success. The importance of research comes in improving the level of muscular ability and the performance of some offensive skills of basketball players using plyometric exercises compounded with weights in modern scientific training methods and means. The aim of this research is to develop compound plyometric exercises with weights and to identify the effect of compound exercises and to improve the level of muscular ability and the performance of some offensive skills of basketball players.The research hypothesized that there is a relationship with statistical indications between compound exercises and improving the level of muscular ability and the performance of some offensive skills of basketball players. The researcher adopted the experimental approach because it suits the nature of the research. As for the research sample, they were talented basketball players in the specialized school affiliated to the Ministry of Sports and Youth, who numbered (12) players, and the researcher conducted tests for some muscular abilities. In the light of the study, the researcher reached a set of conclusions and recommendations to benefit from them in order to reach a higher level.